Ultra‐step‐up dc–dc converter with low‐voltage stress on devices. Issue 3 (28th January 2019) - Jalilzadeh, Tohid; Rostami, Naghi; Babaei, Ebrahim; Maalandish, Mohammad
Abstract : This study suggests a novel ultra‐step‐up dc–dc converter with low normalised voltage stress across the power devices. The proposed converter incorporates the conventional boost converter with a self‐lift circuit and charge pump concept and utilises a voltage multiplier cell at the output side. In the input side, two inductors are magnetised during the switch on‐time. During the switch off‐time, the stored energy in these inductors, charge pump capacitor and input source, is delivered to the load. Accordingly, the proposed converter is capable of providing high voltage gains with a small duty cycle. Besides, the voltage stress across the power devices is low. Therefore, the MOSFET switch with low R DS‐on and devices with reduced nominal voltage can be used which in turn reduces the conduction and turn‐on losses. The analysis of the voltage and current stresses is accomplished. The circuit performance is compared with other solutions in the literature in terms of voltage gain and normalised voltage stress of the semiconductors. Eventually, to validate the theoretical analysis, the experimental results are given.